Molecular diversity of bla-tem homologous genes of cow and chicken farm soils in Perak - Yong, Joseph Ming Wei (2019)
The prevalence of antibiotic-resistant microorganisms has become a global concern both in health care and agribusiness settings. Regardless of the risk revealed by antibiotic resistance, limited information is available regarding the diversity, distribution and origins of resistance genes, especially among environmental bacteria in their natural settings. The aim of this research was to investigate the prevalence and diversity of β-lactamase genes in two different soil ecotypes from animal farm setting via culture-dependent and independent approaches. In this study, soil samples representing ecotypes of cow and chicken farms were collected. A total of fifteen morphologically different bacterial isolates were obtained and characterised. The isolates identified using the API 20 E test and 16S rDNA sequencing in this study belonged to the families Enterobacteriaceae and Pseudomonadaceae. The resistance patterns amongst the isolates varied significantly and phenotypic characteristics of NSBL, ESBL, CMT, pAmpC, and IRT phenotypes were observed. Among the nine β-lactamase genes characterised using PCR, the resistant genes were confined to the bla-TEM and bla-SHV families, with high similarities towards TEM-1 and TEM-116. To further investigate the diversity of the bla-TEM genes, culture-independent approach was performed. High percentage of variants was observed in both animal farm soil samples in which a total of 122 recombinant bla-TEM homologous genes were obtained for cow and chicken farm soils, whereby 32 % were identical to TEM-1 and 4 % to TEM-116. The remaining recombinants (64 %) were demonstrated to be different variants of the known bla-TEM family and were further characterised. Further analysis showed that these variants involved 64 different amino acid substitutions, with up to three amino acid residue modifications. Seven bla-TEM protein sequences resembled TEM-176, whereby a change of amino acid from alanine (A) to valine (V) at position 224 was observed, and five resembled TEM-215, whereby a change from histidine (H) to arginine (R) at position 153 was observed. The remaining 66 bla-TEM protein sequences have at least one amino acid substitution at different positions, however, these substitutions at their respective positions do not correlate with the sequences from the existing database. These observations seemed to suggest that the substitutions may represent novel bla-TEM variants that have arisen through several mutational events. Phylogenetic analysis was carried out to investigate the inferred evolutionary relationships among the gene sequences. Ladder-type phylogenetic topologies were observed in both soil ecotypes, thus suggesting observations that are consistent with the presence of bla-TEM protein sequences with divergent mutations. The results obtained in this study seemed to suggest the prevalence of novel bla-TEM variants in enhancing or maintaining the enzymatic activity in the farm soil ecotypes studied. Resistance genes residing in environmental reservoirs pose serious threat to human health and these results can be used to enhance the understanding of the emergence and dissemination of novel antibiotic resistance from the natural reservoir to the clinical setting, which may aid the development of inhibitors of resistance mechanisms.